2010
DOI: 10.1038/hr.2010.86
|View full text |Cite
|
Sign up to set email alerts
|

Serum phosphate in white-coat hypertensive patients: focus on dipping status and metabolic syndrome

Abstract: Recent studies indicate an association between serum phosphate levels and blood pressure in hypertensive patients. A growing body of evidence suggests that white-coat hypertension (WCH) is associated with target organ damage. Furthermore, metabolic syndrome (MS) and a non-dipping pattern are associated with increased cardiovascular risk. The purpose of this study was to explore the nocturnal blood pressure fall in patients with WCH according to their serum phosphate levels and number of MS components fulfilled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…Surprisingly, in our cohort indices of mineral metabolism correlated with diastolic not with systolic blood pressure. Opposite to our results, Vyssoulis et al in a study of hypertensive adults found positive relation between phosphate concentration and dipping status -highest phosphate status was revealed in "extreme" dippers [28].…”
Section: Agecontrasting
confidence: 99%
“…Surprisingly, in our cohort indices of mineral metabolism correlated with diastolic not with systolic blood pressure. Opposite to our results, Vyssoulis et al in a study of hypertensive adults found positive relation between phosphate concentration and dipping status -highest phosphate status was revealed in "extreme" dippers [28].…”
Section: Agecontrasting
confidence: 99%
“…Then 84 studies were excluded after full-text reading, because of which, 46 studies had no unqualified results, 1 had no full text, and 37 contained patients without exposure to serum ALP or phosphate. Among these excluded ones, Camille P. [11] and Ana Ludimila [12] studied the association between ALP/phosphate and vascular calcification; the research of Jinkwon and his colleagues [13] studied the functional outcomes of cerebrum with ALP and phosphate; Jason P. [14] focused on aortic valve calcification; the study of Gregory [15] was about phosphate and hypertension; and Bernard M.Y [16] investigated the association between alkaline phosphatase and peripheral arterial disease. Finally, a total of 24 trials [16][39] with 147634 individuals were identified from 2011 potentially relevant publications (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…In brief, the majority of the studies showed an inverse relationship between phosphorus status and adiposity, 31, 41, 42, 43, 44, 45, 46, 47, 48, 49 glycemia, 31, 32, 44, 45, 46, 47, 48, 50, 51 lipid profile 32, 47, 51 and blood pressure. 43, 45, 46, 47, 48, 49, 51, 52, 53, 54, 55, 56, 57, 58, 59 …”
Section: Phosphorus and Metabolic Syndromementioning
confidence: 99%